EVALUATION OF DIFFERENT BIOAGENTS AGAINST PHOMOPSIS AINST PHOMOPSIS BLIGHT IN BRINJAL CAUSEDS BY PHOMOPSIS (Sacardo and Syndow) BLIGHT IN BRINJAL CAUSEDS BY PHOMOPSIS (Sacardo and Syndow) - VIJAY KUMAR; TRIPTI PANDEY (The Bioscan, 2019)
A study was conducted in the Department of Plant Pathology, College of Horticulture, (VCSGUUHF) Bharsar. During Kharif season 2016. result revealed that per cent growth inhibition of Phomopsis vexans is maximum in Trichoderma harzianum (62.29%) followed by Bacillus ceresus (53.30%), Pseudomonas fluorescence (48.89%) and minimum per cent inhibition growth was reported in Rhizobium japonicum (42.07%). In vivo result revealed that per cent disease index maximum in Rhizobium japonicum (42.70%) with yield (25.35t/ha) followed by Azotobacter chorococum (39.22%) with yield (26.25t/ha), Bacillus substilis (38.05%) with (26.60t/ha) and minimum Trichoderma harzianum (28.64%) with (28.96t/ha). This result shows that Trichoderma harzianum is very effective bio control agent and should be exploited for the control of Phomopsis blight of Brinjal. So, Trichoderma harzianum @ 5 g/kg seed is maximum effective for the control of phomopsis blight of brinjal.